Rectus sheath hematoma: A review of the literature. (January 2015) - Hatjipetrou, Athanasios; Anyfantakis, Dimitrios; Kastanakis, Miltiades
Abstract: Rectus sheath hematoma (RSH) is a relatively rare clinical condition, strongly associated among others, with abdominal trauma and anticoagulation. Although well documented over the years, it still seems to be often misdiagnosed. Estimations of further increase in incidence are made, based on the increasing use of anticoagulants. Thus it was of interest to us to perform a literature review on the available literature of this entity with the aim to facilitate a better understanding and management in primary and secondary care settings. This review intends to present a synthesis on the main topics of this condition such as pathophysiology, epidemiology, predisposing factors, clinical presentation, diagnosis and basic treatment instructions. The initial search resulted in 146 articles. Additional citations from the reference list of the relevant publication were also included. Every physician in the field of primary/emergency medicine and surgery must be familiar with it, as misdiagnosis may lead to unnecessary laparotomy or death. In contrast, faster and more accurate diagnosis can lead to mortality rate reduction and cost containment. Highlights: Rectus sheath hematoma is a rare clinical condition, frequently misdiagnosed. Increase physicians' awareness on the main topics of this condition. Highlights the need of correct diagnosis in order to reduce complications.